Given that: f(x) = 5x-2. g(x) = (x^1/30 We need to find fog(x) First we will
rewrite fog(x) as follows: fog(x) = f(g(x)) We will substitute with g(x) =
x^1/3 ==> fog(x) = f(x^1/3) Now we will substitute with x^1/3 in f(x) ==>
fog(x) = 5(x^1/3) -2 Now we will substitute with x=-8. ==> fog(x) =
5(-8^1/3) -2 = 5*-2 -2 = -10 -2 = -12 ==> fog(-8) = -12.

We have f(x) = 5x - 2 and g(x) = x^(1/3) [ I have assumed by cubed sqrt you mean raised to the power (1/3)]

We have to find fog( - 8)

fog(x) = f(g(x)) = f( x^(1/3))

=5 * x^(1/3) - 2

For x = -8

fog(-8) = 5*(-8)^(1/3) - 2

=> 5* (-2) - 2

=> -10 - 2

=> -12

**The required result is -12**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.